ChemInform Abstract: Rapid Hydrothermal Synthesis of VO2 (B) and Its Conversion to Thermochromic VO2 (M1). Issue 27 (13th June 2013) - Popuri, Srinivasa Rao; Miclau, Marinela; Artemenko, Alla; Labrugere, Christine; Villesuzanne, Antoine; Pollet, Michael
Abstract The monoclinic layered (B) polymorph of VO2, a promising cathode material for aqueous lithium ion batteries, is hydrothermally synthesized from aqueous mixtures of V2O5 and citric acid (autoclave, 180 °C for 2 h or 220 °C for 1 h).